Cesarotti e Alfieri - Santato, Guido (Quaderni Veneti, 2012)
The paper reconstructs the history of the complex relationship be- tween Vittorio Alfieri and Melchiorre Cesarotti. Alfieri initially held the author of the «Poesie di Ossian» in high esteem, as he considered those poems an excel- lent model for his tragic verse. But Cesarotti’s «Lettera su Ottavia, Timoleone e Merope» caused the firm retort of Alfieri, who defended his stylistic choices, and led to an abrupt change in his attitude.